2008
DOI: 10.2320/matertrans.mra2007232
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Silicon Carbide Sintered with Addition of Boron Carbide, Carbon, and Alumina

Abstract: The thermoelectric properties were examined of SiC specimens prepared by mixing -SiC powder with B 4 C, C, and Al 2 O 3 and then sintering at 2100 C. Sintered specimens containing Al 2 O 3 up to 3% with 0.5% B 4 C and 2.5% C exhibited the highest densities. The electrical conductivities of these specimens increased with the Al 2 O 3 content up to 3%. In contrast, the Seebeck coefficients of these specimens decreased with the addition of 1% Al 2 O 3 , but then barely decreased with the further addition of Al 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Because of their thermoelectric properties, the temperature‐dependent electrical conductivity of α‐ and β‐SiC based materials has been well studied. Ohba et al found that the electrical conductivity of α‐SiC composites containing 5% B 4 C increased from the room‐temperature value of 10 to 550 S/m at 800°C. Due to the n and p type semiconductor nature of α‐SiC and B 4 C, the conductivity of the composite material is lower than that of the pure silicon carbide.…”
Section: Resultsmentioning
confidence: 99%
“…Because of their thermoelectric properties, the temperature‐dependent electrical conductivity of α‐ and β‐SiC based materials has been well studied. Ohba et al found that the electrical conductivity of α‐SiC composites containing 5% B 4 C increased from the room‐temperature value of 10 to 550 S/m at 800°C. Due to the n and p type semiconductor nature of α‐SiC and B 4 C, the conductivity of the composite material is lower than that of the pure silicon carbide.…”
Section: Resultsmentioning
confidence: 99%
“…Besides borides, another group of materials which has been investigated for the use as high temperature thermoelectric applications due to their good thermal stability are carbides [938][939][940][941][942][943][944][945][946][947][948][949][950][951]. Efforts have been focused on the compound SiC which exists in several different modifications, the most prominent being the hexagonal 6-H α-SiC [938,939,947] and the cubic 3-C β-SiC [938,939,[944][945][946][948][949][950]. Depending on the synthesis conditions both p-type and n-type behavior have been reported.…”
Section: Boride and Carbide Thermoelectricsmentioning
confidence: 99%
“…Strategies for improving the thermoelectric properties have included the addition of secondary phases for the fabrication of composite materials, e.g. B 4 C [947], C [945,947], Al 2 O 3 [947], Si 3 N 4 [944], Si [948] and Si/Au/polysilastyrene [948]. Thermoelectric properties of carbide materials in addition to SiC have been reported for layered Mo-based MXene carbides [951], TiC 0.7 C 0.3 [940], flexible WC/polylactic acid composites [941], VC/Cr 23−x Fe x C 6 containing Fe-2.3C-Si-5Mn-7V-8Cr alloy [942] and Zr 2 [Al 3.56 Si 0.44 ]C 5 [943].…”
Section: Boride and Carbide Thermoelectricsmentioning
confidence: 99%
“…6 Moreover, when this was set as the criterion for thermal runaway, we were able to accurately predict the onset temperature of thermal runaway of all the flash sintering experiments in the literature. As already noted [11][12][13] (OÁm), q q 0 2.9391 9 10 À7 3.3 9 10 À3 3.7 9 10 À4 10 À5 E a 1.481 eV Thermal conductivity 11,13,14 [WÁ(mÁk) À1 ], j 41 0.3 2.7 200 Volumetric heat capacity [13][14][15] (JÁcm À3 ÁK À1 ), c 3.852 0.0368 0.1103 1.534 Emissivity, e in the last section, this also holds for the mold-assisted flash sintering: In the power panel of Fig. 2(b), sample's self Joule heating and radiation heating curves intersect at a time that essentially coincides when thermal runaway occurs.…”
Section: Onset Criterion For Thermal Runawaymentioning
confidence: 54%